'It's quite a complex trail for families now' – Provider understanding of access to services for Aboriginal children with a disability. (June 2021) - Green, Anna; Abbott, Penelope; Luckett, Tim; Davidson, Patricia Mary; Delaney, John; Delaney, Patricia; Gunasekera, Hasantha; DiGiacomo, Michelle
Aboriginal and Torres Strait Islander children experience a higher prevalence of disability and socio-economic disadvantage than other Australian children. Early intervention from across the health, education and social service sectors is vital for improving outcomes, but families face a number of barriers to service access which impede intervention. This study aimed to inform ways to improve access to services for families of urban-dwelling Aboriginal children with a range of disabilities. A qualitative approach was taken to explore providers' perceptions of factors that either impeded or enabled families' access to services. In this research, the term 'provider' refers to individuals who are employed in a range of sectors to deliver a service involving assessment or management of an individual with a disability. Semi-structured in-depth interviews with 24 providers were conducted. Data analysis was informed by the general inductive approach and then applied deductively to the candidacy framework to generate additional insights. Candidacy focuses on how potential users access the services they need and acknowledges the joint negotiation between families and providers regarding such access. Our research identified that candidacy was influenced by the historical legacy of colonisation and its ongoing socio-cultural impact on Aboriginal people, as well as funding and current policy directives. Enacting culturally sensitive and meaningful engagement to better understand families' needs and preferences for support, as well as support for providers to develop their understanding of family contexts, will contribute to facilitating service access for Aboriginal children with a disability.